Double trouble: Psychiatric comorbidity and opioid addiction—All-cause and cause-specific mortality. (1st March 2015) - Bogdanowicz, Karolina M.; Stewart, Robert; Broadbent, Matthew; Hatch, Stephani L.; Hotopf, Matthew; Strang, John; Hayes, Richard D
Highlights: The influence of psychiatric comorbidity in opioid dependency is unclear. We examine mortality risk and psychiatric comorbidity in 4837 opioid dependent patients. Comorbid alcohol use disorder increases risk of fatal overdose and hepatic deaths. Comorbid personality disorder increases risk of liver related deaths. Assessment for personality and alcohol problems in opioid dependent patients is key. Abstract: Background: Opioid misusers have recognized high mortality but the influence of psychiatric comorbidity in excess cause-specific mortality is unclear. Methods: Opioid use disorder (OUD) patients were identified in the South London and Maudsley Case Register. Deaths were identified through database linkage to the national mortality dataset. Standard mortality ratios were calculated to compare mortality risk with the general population. Cox and competing risk regression models were used to investigate the effect of psychiatric comorbidity and psychological health on all-cause and cause-specific mortality (respectively) in OUD patients. Results: Of 4837 OUD patients, 176 had died. Mortality rates were substantially higher than the general population (SMR 4.23; 95%CI 3.63–4.90). Among those with OUD, comorbid personality disorder (PD) and comorbid alcohol use disorder (AUD) was associated with increased all-cause mortality in all models, including the fully adjusted model, controlling for socio-demographic factors, severity of drug use, risk behaviours and physical health (HR2.15, 95%CI 1.17–3.95; HR2.28, 95%CI 1.54–3.36). AUD was associated with increased risk of fatal overdose (HR2.57, 95%CI 1.26–5.26) and hepatic-related deaths (HR7.26, 95%CI 2.79–18.86). Individuals with OUD and comorbid PD had almost four times greater risk of liver related deaths compared to those without PD (HR3.76, 95%CI 1.21–11.74). Comorbid severe mental illness and poor psychological health were not associated with increased mortality. Conclusions: This study highlights the importance of assessment for PD and AUD in OUD patients in order to identify individuals at substantially elevated mortality risk to enable a more personalized approach to their medical care.